A neoliberal transformation or the revival of ancient healing? A critical analysis of traditional Chinese medicine discourse on Chinese television. Issue 5 (20th October 2022) - Zhu, Ge
ABSTRACT: Neoliberalism has profoundly shaped health discourse and promotion in Western countries, and scholars have also begun applying the hegemonic global ideology and framework of governance to study the non-Western world. This paper examines Traditional Chinese Medicine (TCM) discourse on China's mainstream television through the theoretical lens of neoliberalism. A critical discourse analysis finds that the 'actively responsible individual', the central notion of neoliberal health promotion, is deeply embedded in the rhetoric of traditional medicine and interwoven with the entrenched cultural values and beliefs. Media exploit the ancient healing philosophy to cultivate consumerist desires and exhort people to engage in self-care and self-medicine. By imposing expert authority, emphasizing conventional expectations, and exerting traditional moralities, media imperceptibly installed the neoliberal value of self-regulation and shaped individual conduct without challenging, and even reinforcing, the predominant political ideology and mainstream culture. The findings contribute to the understanding of health promotion in contemporary China and provide some evidence for the academic debate on the validity of applying neoliberalism to study China.